HUBUNGAN SELF EFFICACY TERHADAP KEPATUHAN DIIT PADA PENDERITA DM - Hilda Rahmi Ningsih; Bayhakki Bayhakki; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Self-efficacyis the attitude of confidence or confidence in his own ability to display behavior that lead one to the expected results. The purpose of this study was to determine the relationship of self efficacy of compliance with diet in patients with DM at Arifin Achmad Pekanbaru. The design of this study using a correlation at study with cross sectional approach. Samples were 40 respondents taken based on inclusion criteria using cluster sampling. The measuring instrument used was a questionnaire, in which the self-efficacy variables using questionnaires DMSES and a compliance questionnaire for the variable compliance diet DM. The analysis used univariate analysis to determine the frequency distribution and bivariate using chi square test. The results showed that 15 respondents who had high self-efficacy was obedient in performing diet DM as many as 14 respondents (70%) and of the 25 respondents who had low self-efficacy , with better adherence to diet DM as many as 6 people respondents (30%). Statistical test results obtained p value of 0.000 where p value < alpha (0.05), so there was a significant association between self-efficacy with diet adherence in patients with DM at Arifin Achmad Pekanbaru. Further research is suggested to examine other variables using different research design.Keywords: Diabetes, diet compliance, self-efficacy